A Community Empowerment Approach to Heritage Management From Values Assessment to Local Engagement - Kyriakidis, Evangelos (Taylor & Francis, 2020)
This book presents an innovative approach to public archaeology in a rural community, which has had powerful results in terms of empowering a village community in Crete to become long-term guardians of their cultural heritage. Highlighting the theoretical and local contexts of the Philioremos Peak Sanctuary Public Archeology Project, this book explores the methodology and the project outcomes, and assesses best practice in the field of public archaeology within a rural community. As well as expanding the research on Minoan peak sanctuaries, the volume contributes to a greater understanding of how rural communities can be successfully engaged in the management of heritage, and is relevant to archaeologists and other heritage professionals wishing to understand the latest developments in public archaeology.